Interrogating Gender Texts: A Critical Review of the Literature - Leona M. English; Catherine J. Irving; Kerrie Kennedy (Adult Education Research Conference, 2007)
This paper synthesizes the Canadian adult education literature related to gender and adult learning. By examining how it has been written about, what it focuses on, and what the gaps are, the authors identified current contributions in the Canadian literature.